PERAN MEDI ASI MODAL PSI KOLOGI S: HUBUNGAN ANTARA KEPEMI MPI NAN AUTENTI K DAN KOMI TMEN ORGANI SASI ONAL STUDI PADA RUMAH SAKI T JI WA DAERAH SURAKARTA DAN RUMAH SAKI T PKU MUHAMMADI YAH SURAKARTA - Yosephin Dila Sintka Sekar Palupi; Nang Among Budiadi; Sugiyarmasto .; Ariefah Yulandari (Fakultas Ekonomi - Universitas Setia Budi, 2020)
This study aims to examine the mediating role of pshychological capital in the rlationship between authentic leadership and organizational commitment. Organizational commitment is an important factor in improving hospital performance. Commitment as a type of pshchological bond that reflects the dedication and responbility of employees to the work targets and goals of the hospital so that when organizational commitment is built the hospital will lead to various beneficial results. Data was obtained through distributing questionnaires to employees who worked at Surakarta Regional Mental Hospital and PKU Muhammadiyah Surakarta Hospital. The research sample used amounted to 159. The sampling technique used in this study was the Cluster Sampling technique. Hypothesis testing is done using regression analysis with mediating variables. The results in this study indicate that authentic leadership has a positive and significant effect on organizational commitment, authentic leadership has a positive and significant effect on psychological capital, psychological capital has a positive and significant effect on organizational commitment. This means psychological capital mediates the relationship between authentic leadership and psychological capital